René Girard on the Decalogue 2 - Girard, René (Pierpaolo Antonello, 2009)
French critical thinker and anthropologist, René Girard discusses with Pierpaolo Antonello (U of Cambridge) some historical aspects of the ten commandments and their Christian redefinition.